STOCK RETURN DETERMINANTS FOR COMPANY LISTED IN BUSINESS-27 INDEX - Susilawaty, Lilis; Simbolon, Ika Pratiwi; Laurensia, Stephanie (Universitas Multimedia Nusantara, 2024)
Abstract-This paper investigates the effect of firm size, Bank Indonesia's 7-days reverse repo rate and foreign exchange reserves on the stock return of companies listed in Business-27 Index by using multiple regression analysis. Based on the findings of this study, all of the independent variables have significant effect on the stock return both partially and simultaneously. The findings of this study are expected to help investors make appropriate investment decisions for investing in stocks. This study has several limitations, there's no study of external (foreign) factors as independent variables, or stock returns of other countries such as developed countries. Researchers who want to conduct research with the same topic are expected to use other variables more specific to stock returns. It is hoped that further research will more focus on other factors that can affect stock returns. Keywords: BI 7-Day Reverse Repo Rate; Firm Size; Foreign Exchange Reserves; Stock Return